Posted by Sira on Tuesday, May 8, 2012 at 1:27am.
- 3 x + z = - 3 Add 3 x to both sides
- 3 x + 3 x + z = - 3 + 3 x
z = 3 x - 3
x - 2 y - 3 z = - 5
x - 2 y - 3 * ( 3 x - 3
) = - 5
x - 2 y - 3 * 3 x - 3 * ( - 3 = - 5
x - 2 y - 9 x + 9 = - 5
- 8 x - 2 y + 9 = - 5 Add 8 x - 9 to both sides
- 8 x - 2 y + 9 + 8 x - 9 = - 5 + 8 x - 9
- 2 y = - 14 + 8 x Divide both sides by - 2
y = - 14 / - 2 + 8 x / - 2
y = 7 - 4 x
2 x - y + 2 z = 11
2 x - ( 7 - 4 x ) + 2 * ( 3 x - 3 ) = 11
2 x - 7 + 4 x + 6 x - 6 = 11
12 x - 13 = 11 Add 13 to both sides
12 x - 13 + 13 = 11 + 13
12 x = 24 Divide both sides by 12
x = 24 / 12
x = 2
y = 7 - 4 x
y = 7 - 4 * 2
y = 7 - 8
y = - 1
z = 3 x - 3
z = 3 * 2 - 3
z = 6 - 3
z = 3
Solution :
x = 2 , y = - 1 , z = 3